MAKNA SIMBOLIK GERAKAN TARIAN SUFI TURKI JALALUDIN RUMI (1203-1273M): ANALISIS SEMIOTIKA CHARLES SANDER PIERCE - Razqan Anadh Mahendar (CMES (Center of Middle Eastern Studies), 2017)
This research discussed : (1) How the sufi dance lasts? (2) What is the symbolic meaning of sufi dance movements and it‟s message that wanted to be delivered ? This research used qualitative method which is presented descriptively by describe Sufism in general, Sufism flow, Sufism development, describe Sufi dance in term of it‟s development, symbolic meaning are the meaning of sufi dance movement and the clothing which were worn by the sufi dancers. Based on the result of this research conclude  are  : first, sufi dance is identic with Sufism and the figures who influence this dance. Second, sufi dance movements have a message that wanted to be delivered to everyone. Third, sufi dance has a function as syi‘ar of Islam.